If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 2 = 12x Reorder the terms: 2 + 7x = 12x Solving 2 + 7x = 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. 2 + 7x + -12x = 12x + -12x Combine like terms: 7x + -12x = -5x 2 + -5x = 12x + -12x Combine like terms: 12x + -12x = 0 2 + -5x = 0 Add '-2' to each side of the equation. 2 + -2 + -5x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -5x = 0 + -2 -5x = 0 + -2 Combine like terms: 0 + -2 = -2 -5x = -2 Divide each side by '-5'. x = 0.4 Simplifying x = 0.4
| (x+2)2=y | | 5+2(5x-4)=7-5(2x+1) | | (2x-1)(4x+3)=7-22x | | ln(x+12)+ln(2)=2ln(x) | | 7+2(3x-4)=5-4(2x+1) | | (6-y)+(1+4y)=43 | | 16+(-24)+12= | | 4x^2=-20x | | 48a^2-8ab-8b^2=0 | | x(x-3)=7 | | x^2-9x+5=x^2-3x-4 | | 28x^2-22x=0 | | 9x(x+5)=0 | | 3x-8=7x+9 | | 5y^2-11=0 | | 6m+w=72m^2 | | 5a-4=6a+12 | | 9x(x+9)=0 | | x^2+15x-21=0 | | 6(3y-2(y-1))-2+7y=0 | | 1x=32x-3 | | 5(5-3x)=12-4(x-3) | | x^2=-48 | | 4y^2-6=5y | | 2lnx+ln(2x-1)=ln(5x+2) | | 5x+20=2x-10(x+10) | | 5x+20=2x-10 | | (4x-3)(3x+5)= | | 5x+20=65 | | 3m+2n+2= | | 8p^2=-56p | | 4*6*x+(6x*5x)= |